Republic of Poland : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper considers the case of Poland to analyze global financial spillovers to emerging market (EM) sovereign bond markets. Foreign holdings of Polish government bonds have increased substantially over the last decade. Although foreign participation in local-currency sovereign bond markets provides an additional source of financing and reduces sovereign yields, it has also given rise to concerns about increased sensitivity to shifts in market sentiment. The analysis in this paper suggests that foreign participation plays an important role in transmitting global financial shocks to local-currency sovereign bond markets by increasing yield volatility and, beyond a certain threshold, amplifying these spillovers.